Exploratory analysis of long-term suppressive therapy with dalbavancin in ventricular assist device infections caused by Staphylococcus aureus - Morath, Benedict; Klein, Sabrina; Chiriac, Ute; Müller, Yvonne; Köppel, Lisa; Frey, Otto; Lanzinger, Heike; Schlegel, Philipp; Hamed, Sonja; Nurjadi, Dennis; Ehlermann, Philipp; Karck, Matthias; et al. (Scientific reports, 2025)
To analyze dalbavancin’s potential for long-term suppressive therapy in patients with infected ventricular assist devices (VAD), the VAD register of Heidelberg University Hospital was searched for patients who received dalbavancin for long-term suppression therapy. Clinical data, laboratory, and microbiological results were extracted. Healthcare utilization was analyzed by number of hospitalizations before and during dalbavancin therapy with a generalized linear mixed model. Drug safety was investigated with regard to liver and renal function, and thrombocyte count. Thirteen patients were included in the study; receiving a regimen of 1500 mg dalbavancin at day 1 and day 8 with repetition of the cycle at day 42. The mean follow-up time was 254 days (IQR 252). Eight patients were treated for driveline infection and five patients for driveline and blood stream infection, all of them caused by Staphylococcus aureus. The majority of patients (n = 11/13) underwent surgical wound debridement and intravenous antibiotic therapy before start of dalbavancin. Under dalbavancin therapy, no blood stream infection was observed and significantly fewer hospitalizations occurred with an odds ratio of 0.27 (p < 0.001). In four patients, elevations of liver transaminases were detected and led to discontinuation of dalbavancin therapy in one patient.
Gesehen am 29.10.2025